Efficacy analysis of early bilateral decompressive craniectomy for severe traumatic brain injury - Feng-lei SONG; Yang ZHAO; Lin MA; Li-gang WANG; Bo-feng LIU; Peng SUN; Yun-cai SHANG; Guang-yi WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Objective To investigate the efficacy and safety of predictive early bilateral decompressive craniectomy in the treatment of severe traumatic brain injury (sTBI). Methods A total of 92 patients with sTBI underwent predictive early bilateral decompressive craniectomy (observation group, N = 42) and conservative first-line treatment followed by unilateral or bilateral decompressive craniectomy (control group, N = 50). Intracranial pressure (ICP) before and after treatment was monitored, Glasgow Outcome Scale (GOS) was used to evaluate prognosis, and postoperative complications were recorded. Results The observation group patients had less time interval than control group patients [(4.63 ± 1.61) h vs. (36.61 ± 1.92) h; t = 32.464, P = 0.001]. Compared with before operation, ICP decreased 1 d after operation (P = 0.001), and continued to decrease 7 d after operation (P = 0.001) in both groups. Compared with control group, the ICP in observation group patients decreased more (P = 0.001). Of 92 patients, 37 had a good prognosis (40.22% ) and 55 had a poor prognosis (59.78% ). The rate of good prognosis in observation group was significantly higher than that in control group [54.76% (23/42) vs. 28% (14/50); χ2 = 5.697, P = 0.017]. The good prognosis rate of patients less than 41 years old was significantly higher than that of patients older than 41 years old ( χ2 = 5.526, P = 0.025). Of 92 patients, 31 (33.70% ) had postoperative complications, including 11 cases (11.96% ) of subdural effusion, 4 cases (4.35% ) of intracranial hemorrhage, 3 cases (3.26%) of hydrocephalus, 4 cases (4.35%) of infection, 2 cases (2.17%) of epilepsy and 7 cases (7.61% ) of organ dysfunction. The postoperative complication rate in observation group was lower than that in control group [21.43% (9/42) vs. 44% (22/50); χ2 = 5.205, P = 0.022]. Conclusions Predictive early bilateral decompressive craniectomy for sTBI could reduce ICP, prevent delayed intracranial hematoma caused by unilateral decompressive craniectomy, significantly improve the prognosis, decrease the incidence of postoperative complications, and improve the patients' quality of life.